Efficacy, safety and usability of bronchial artery embolization using a new anti-reflux microcatheter in the management of haemoptysis - Angileri, Salvatore Alessio; Rodà, Giovanni Maria; Arrichiello, Antonio; Signorelli, Giulia; Di Meglio, Letizia; Gurgitano, Martina; Di Bartolomeo, Francesco; Ierardi, Anna Maria; Paolucci, Aldo; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2020)
Purpose: Haemoptysis (Hp) is a potentially life-threatening medical condition. We investigated the safety, efficacy and usability of bronchial artery embolization using a new anti-reflux microcatheter in patients with haemoptysis. Materials and methods: The study was held as a single-center retrospective study. Four patients underwent bronchial arterial embolization, using the new microcatheter. Then, we evalueted technical success, immediate clinical success, haemoptysis recurrance rate and safety in reducing reflux complications. Conclusion Bronchial artery embolization for hemoptysis with the new microcatheter is a safe and effective method with high technical and clinical success rates. Short and medium-term results are excellent.